2016
DOI: 10.1177/0269216315625860
|View full text |Cite
|
Sign up to set email alerts
|

‘I think you just learnt as you went along’ – community clergy’s experiences of and attitudes towards caring for dying people: A pilot study

Abstract: Creating opportunities for clergy and palliative care staff to meet and undertake shared training will enhance the quality and level of care for people dying at home who wish to receive spiritual support. Enabling clergy to develop links with local palliative care centres will enhance confidence for both clergy and staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
5
0
6
Order By: Relevance
“…Fifty-three articles were included [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85]. Seventeen were quantitative studies [33,34,36,37,40,43,50,51,54,61,66,67,69,71,74,81,82], of which the majority ( n = 11) were survey studies, 27 qualitative studies […”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-three articles were included [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85]. Seventeen were quantitative studies [33,34,36,37,40,43,50,51,54,61,66,67,69,71,74,81,82], of which the majority ( n = 11) were survey studies, 27 qualitative studies […”
Section: Resultsmentioning
confidence: 99%
“…Seventeen were quantitative studies [33,34,36,37,40,43,50,51,54,61,66,67,69,71,74,81,82], of which the majority ( n = 11) were survey studies, 27 qualitative studies [38,39,41,42,44,45,46,48,49,53,55,56,57,58,59,60,63,64,68,73,76,78,79,80,83,84,85], most of which were interview studies ( n = 13), and nine mixed-methods studies [35,47,52,62,65,70,72,75,77]. Most studies were conducted in Western Europe ( n = 37), especially in the UK ( n = 10), Germany ( n = 8), and the Netherlands ( n = 13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are increasingly becoming involved in spiritual care in the community and in general practice. In a pilot study community clergy who received training with healthcare professionals and chaplains enhanced the quality of care they provided to patients dying at home who wished to receive spiritual support 12 and, in a previously mentioned study, it was suggested that primary care chaplaincy could be considered as an alternative to cognitive behavioural therapy. 4 Perhaps in future the GP will be regarded as the generalist in spiritual care who refers appropriate patients to the chaplain, who is the specialist in spiritual issues.…”
Section: Do Chaplains Have a Role In General Practice?mentioning
confidence: 99%
“…Varias investigaciones asumen por espiritualidad la definición acuñada en el año 2011 por la European Association of Palliative Care (EAPC) o una muy similar, esto es, la dimensión dinámica de la vida humana que se relaciona con el modo en que las personas (individuocomunidad) experimentan, expresan o buscan significado, propósito-trascendencia, y el modo de conectarse con el momento, el "yo", los otros, la naturaleza, lo significativo o lo sacro (4,(13)(14)(15)(16)(17)(18)(19)(20)(21). También, la espiritualidad ha sido definida como un sentido de paz individual, objetivo y conexión con otros, y creencias en relación con el sentido de la vida y la muerte que pueden ser expresadas a través de la religión u otros medios; además, es de carácter universal (22,23).…”
Section: Resultsunclassified